2019
DOI: 10.1136/annrheumdis-2019-215195
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of OX40 in the regulation of autoantibody sialylation in arthritis

Abstract: ObjectiveAn increased proportion of circulating follicular helper T (Tfh) cells was reported in rheumatoid arthritis (RA), but it remains uncertain how Tfh cells affect antibody hyposialylation. We investigated the regulation of autoantibody hyposialylation by Tfh cells in RA using murine model.MethodsBehaviours of Tfh cells and their function on B cell promotion were analysed. Change of arthritogenicity and sialylation of autoantibodies during the course of arthritis was examined by mass spectrometry. Tfh-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…cTfh17 than healthy controls. We also found that frequency of cTfh17 cells were higher than osteoarthritis patients and had positive correlation with ACPA titers in patients with treatment naïve RA [32]. They also highly expressed OX40 on their surface.…”
Section: Rheumatoid Arthritissupporting
confidence: 54%
See 4 more Smart Citations
“…cTfh17 than healthy controls. We also found that frequency of cTfh17 cells were higher than osteoarthritis patients and had positive correlation with ACPA titers in patients with treatment naïve RA [32]. They also highly expressed OX40 on their surface.…”
Section: Rheumatoid Arthritissupporting
confidence: 54%
“…Increase of Tfh cells in secondary lymphoid organs of mice was reported in plural models [30][31][32]. Among them, we recently reported specific increase of Tfh17 cells in arthritis onset in glucose-6-phosphate isomerase induced arthritis [32]. They seemed to contribute to the disease development by promotion of autoantibody production and regulation of their chemical modification via OX40, which was highly expressed on Tfh17 cells.…”
Section: Rheumatoid Arthritismentioning
confidence: 91%
See 3 more Smart Citations